IPV6 Packet Transmission for High Speed Networks (International Journal of Communication Systems and Network Technologies, 2013)
IPV6 is a new technology that has been developing as a replacement for existing Internet protocol, IPV4. IPV6 was designed with same additional features to the IPV4. In order to meet the requirement of fast growing internet, we must switch from IPV4 to IPV6. IPV6 is a datagram protocol same as IPV4 having 128 bit addresses instead of 32 bit in IPV4. The Internet Protocol Version 6 (IPv6) becomes the next-generation Internet protocol, and was originally proposed due to the scarcity of the IPv4 address space. To transmit lage IPV6 packet on short time, we can use Gigabit Ethernet. The CRC calculation is a core part of the Ethernet processing. CRC is used to generate a checksum over the whole frame at transmission and to check that the frame is still correct at reception. Gigabit is a popular broadband technology for good reason. It can transfer large amounts of data through a large network at high speeds. It uses full duplex bidirectional links, each side of the link must be capable of computing two CRC checksums at the same time, one for the transmitted frame. Here the CRC processing time is very much reduced.
Keywords: CRC; Gigabit Ethernet; IPV6; Ethernet Frame